2012
DOI: 10.4236/ojas.2012.23025
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of genetic diversity and conservation priorities for Egyptian chickens

Abstract: In this study, 21 microsatellite markers were used to genotype 196 Egyptian local chickens obtained from Fayoumi (n = 35), Dandarawy (n = 30), Baladi (n = 29), Sinai (n = 30), El-Salam (n = 36), and Golden Montazah (n = 36) strains. The results were compared to two pure commercial chicken populations reared in Japan-White Leghorn (n = 42) and Rhode Island Red (n = 43). A total of 162 alleles were observed, with an average of 7.7 alleles per locus. The average expected heterozygosity for the Egyptian chickens w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
38
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 27 publications
7
38
6
1
Order By: Relevance
“…the locus LEI0234 had three private alleles in two distant populations). In the current study, 13.18% of specific alleles were slightly lower than those previously reported in Egyptian local chicken breeds which showed a range of 16.04% (Ramadan et al, 2012) to 45.28 % (Roushdy et al, 2012a) of total observed alleles. Regarding the private alleles as previously reported in Sinai chicken populations, a minimum value of 2 and a maximum value of 4 specific alleles were observed by Ramadan et al (2012) and El-Tanany et al (2011), respectively.…”
Section: Discussioncontrasting
confidence: 79%
See 4 more Smart Citations
“…the locus LEI0234 had three private alleles in two distant populations). In the current study, 13.18% of specific alleles were slightly lower than those previously reported in Egyptian local chicken breeds which showed a range of 16.04% (Ramadan et al, 2012) to 45.28 % (Roushdy et al, 2012a) of total observed alleles. Regarding the private alleles as previously reported in Sinai chicken populations, a minimum value of 2 and a maximum value of 4 specific alleles were observed by Ramadan et al (2012) and El-Tanany et al (2011), respectively.…”
Section: Discussioncontrasting
confidence: 79%
“…Generally, local Egyptian chicken breeds yielded MNA/breed per locus which ranged between 2.33 and 6.67 using different numbers of loci, breeds and sampled individuals. The mean value of effective alleles/ locus were cited in the range of 2.9 -5.232 (Roushdy et al, 2013b;Roushdy et al, 2012a), while mean effective number of alleles per breed previously detected in Sinai chickens ranged from 1.774 (Farrag et al, 2013) to 3.4 (Ramadan et al, 2012). This indicates that our results revealed higher effective number of alleles (6.343) than previous studies.…”
Section: Discussionsupporting
confidence: 43%
See 3 more Smart Citations